N-acetylcysteine and vancomycin alone and in combination against staphylococci biofilm - Leite, Bruna; Gomes, Fernanda; Melo, Poliana [UNESP]; Souza, Clovis; Teixeira, Pilar; Oliveira, Rosário; Pizzolitto, Elisabeth [UNESP] (Editora Cubo, 2013)
Introduction: The ability of staphylococci to produce biofilm is an important virulence mechanism that allows bacteria both to adhere and to live on artificial surfaces and to resist to the host immune factors and antibiotics. Staphylococcal infections have become increasingly difficult to treat due their antibiotic resistance. Therefore, there is a continuous need for new and effective treatment alternatives against staphylococcal infections. The main goal of this study was to test N-acetylcysteine (NAC) and vancomycin alone and in combination against S. epidermidis and S. aureus biofilms. Methods: Biofilms were treated with NAC at minimum inhibitory concentration (MIC) and 10 × MIC concentrations and vancomycin at MIC and peak serum concentrations. Results: The use of NAC 10 × MIC alone showed a significant antibactericidal effect, promoting a 4-5 log10 CFU/ mL reduction in biofilm cells. The combination of NAC 10 × MIC with vancomycin (independently of the concentration used) reduced significantly the number of biofilm cells for all strains evaluated (5-6 log10). Conclusion: N-acetylcysteine associated to vancomycin can be a potential therapeutic strategy in the treatment of infections associated to biofilms of S. epidermidis or S. aureus.
Keywords: Biofilm; N-acetylcysteine; Staphylococcus aureus; Staphylococcus epidermidis; Vancomycin; Antibiotic resistance; Artificial surfaces; Minimum inhibitory concentration; Therapeutic strategy; Antibiotics; Bacteria; Enzyme inhibition; Biofilms